2000
DOI: 10.1144/petgeo.6.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on clay smear formation along faults

Abstract: A ring shear apparatus was used to investigate the development of clay smear along faults in sand–clay sequences. Experiments were performed, using six different clay types, different stress conditions (σ n =6–500 kPa) and different amounts of clay (4 and 12.5%). The development of clay smear seems to depend on the competence contrast between the clay and the surrounding sand. Clay, when it is less competent than sand, behaves in a ductile manner, resulting in the development of clay sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…To reproduce faults in artificial sand/clay successions, ring samples were assembled that consisted of a block of clay sandwiched by a ringed block of sand [Weber et al, 1978;Sperrevik et al, 2000;Clausen and Gabrielsen, 2002]. These experiments were successful in forming clay smears that thinned with increasing throw.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reproduce faults in artificial sand/clay successions, ring samples were assembled that consisted of a block of clay sandwiched by a ringed block of sand [Weber et al, 1978;Sperrevik et al, 2000;Clausen and Gabrielsen, 2002]. These experiments were successful in forming clay smears that thinned with increasing throw.…”
Section: Methodsmentioning
confidence: 99%
“…As Sperrevik et al [2000] and Clausen and Gabrielsen [2002] pointed out, the competency contrast between the sandstone and the low-permeability layer is crucial to smear production. In this study, even though the Berea sandstone was much lithified compared to the siltstone, changing the effective normal pressure s neff would change the contact area (asperity) of the sandstone smear on the precut surface.…”
Section: Possible Stress Dependence Of Fault Seal Potentialmentioning
confidence: 99%
“…The continuity of smears may be influenced by factors such as fault throw, thickness of source layer, fault geometry (extensional v. contractional dip relay), rock properties at the time of deformation, and contrast in mechanical strength between shale and non-shale lithologies. Experiments carried out using a ring shear apparatus have shown that the competence contrast between the clay and the surrounding lithology (sand in the experiments) is one major control on the continuity of the smear (Sperrevik et al 2000). In experiments where the sand had low shear strength, the clay behaved in a brittle manner and produced no smear.…”
Section: Fault Throw and The Continuity Of Smearmentioning
confidence: 98%
“…Aydin and Johnson,1978;Fossen and Hesthammer, 1998), clay/shale smearing (e.g. Lindsay et al, 1993;Yielding et al, 1997;Sperrevik et al, 2000;Faerseth, 2006), cementation (e.g. Knipe, 1993;Sverdrup and Bjørlykke, 1997;Hesthammer et al, 2002;Fisher et al, 2003), and pressure solution (e.g.…”
Section: Fault Sealmentioning
confidence: 99%